Tinjauan Hukum Terhadap Praktik Penanganan Perkara Tindakan Faktual yang Didahului Dengan Surat Permohonan Penerbitan Sertifikat Terhadap Terbitnya SEMA Nomor 2 Tahun 2024: Studi Komparatif Putusan Nomor 93/G/TF/2023/PTUN.BDG dan 41/G/TF/2024/PTUN.BDG - Theo Yonathan Simon Laturiuw; Rotua Valentina Sagala (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This research examines the practice of handling Factual Action (TF) cases at the State Administrative Court (PTUN) after the issuance of Supreme Court Regulation Number 2 of 2019 and the Job Creation Law, as well as the implications for the issuance of SEMA Number 2 of 2024. The main focus is on Factual Action (TF) cases which are preceded by a letter requesting the issuance of a certificate with a comparative study of Decision Number 93/G/TF/2023/PTUN.BDG and  41/G/TF/2024/PTUN.BDG.  This research aims to analyze whether TF cases that are preceded by an application for issuing a certificate are a form of smuggling in Negative Fictitious or Positive Fictitious cases, or whether they have their own classification because there are unique characteristics that differentiate them.  The research method used is a normative legal research method with a case study approach.  The research results show that there are two models for handling TF cases which are preceded by a request for certificate issuance.  The two are different because the first model can be considered as Positive Fictitious/Negative Fictitious legal smuggling, but the second model is not legal smuggling.  This means that the existence of factual action cases has produced various types of factual actions with their own unique characteristics.  These cases are not always smuggling Positive Fictitious or Negative Fictitious cases, but have unique characteristics that need to be recognized and accommodated in the practice of state administrative justice.